2020
DOI: 10.1186/s12885-020-6590-4
|View full text |Cite
|
Sign up to set email alerts
|

Rectal aberrant crypt foci (ACF) as a predictor of benign and malignant neoplastic lesions in the large intestine

Abstract: Background: The importance of ACF is not fully explained, however, their number may be a good predictor of synchronous and metachronic adenoma or other polyps whose removal reduces the risk of CRC. Due to the epidemiological and genetic association of ACF with pre-cancer lesions, they may be a potential CRC biomarker. The aim of our study was to show that the number and type of rectal ACF may be a good predictive factor for the presence of polyps located proximally from the splenic flexure and that the type an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…The number of aberrant crypts in ACF might be determinant for the progression of colorectal carcinogenesis. [39] Within this context, BA at all doses tested reduced the number of aberrant crypts and ACF. In addition, the results revealed that this chemoprotective effect is related to the inhibition of COX-2 and PCNA expression.…”
Section: Discussionmentioning
confidence: 91%
“…The number of aberrant crypts in ACF might be determinant for the progression of colorectal carcinogenesis. [39] Within this context, BA at all doses tested reduced the number of aberrant crypts and ACF. In addition, the results revealed that this chemoprotective effect is related to the inhibition of COX-2 and PCNA expression.…”
Section: Discussionmentioning
confidence: 91%
“…It should also be remembered that it is possible to transform ACF in different sections of the colon into adenomas, hyperlpastic polyps or “serrated polyps” [ 6 , 45 , 46 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to chronic inflammation, fibrosis or anarchic cell proliferation, architectural crypt distortions are observed in both CRC and IBD. This phenomenon is called "aberrant crypt foci" (ACF) or "corrupted colonic crypts" (CCC), respectively [69][70][71][72]. Alterations of the crypt morphologies, accompanied by the fragmented mucus layer, have been described in CRC samples since the 1980s [73,74].…”
Section: Topography Physiological Description and Pathological Evolutmentioning
confidence: 99%